(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
Bangladesh and India Sharing fifty-four trans-boundary rivers water that flows from India to Bangladesh. Bangladesh is mostly dependent on India for their water and has no control over the water shed management policy of the rivers. Being a smaller, weaker military and economy than India, Bangladesh cannot influence the watershed management policies and face floods and water scarcity, reducing yield production and fish productivity, an ecological imbalance in estuarine areas, saline water intrusion in the southwestern part of Bangladesh and reduced navigation. Water governance is the combination of the political, social, economic and administrative system, which manage the water resources and provide services in the different level of society. Based on the water governance definition the researchers find out the different stakeholder in the management of water governance and the lack of practices of the theoretical concept of water governance and try to indicate the possibilities of the better solutions (Conflict or cooperation) of this trans-boundary water conflicts between both countries. The paper also compared the present negotiation process with different kinds of modes of wicked problem in water resource management. The study recommends few suggestions to minimize the conflict over the utilization of trans-boundary water resources management for example, a hydro-community like EU water framework Directive that is based on the soft power of peer review rather than a penalizing measure. Int. J. Agril. Res. Innov. & Tech. 8 (1): 79-84, June, 2018